A novel approach to remote sensing of vegetation - Bidyuk, P.I.; Litvinenko, V.I.; Ponomarenko, S.O. (Навчально-науковий комплекс "Інститут прикладного системного аналізу" НТУУ "КПІ" МОН та НАН України, 2005)
The problem of remote estimation of chlorophyll content in vegetation is considered. Some reflectance spectra have been recorded for winter wheat leaves with various level of chlorophyll concentration. To reduce the level of noise in the measurement data produced by measuring system and possible influence of soil surface smoothing procedure proposed by Savitzky and Golay was applied. The 1st derivative of reflec-tance spectra curves had been computed and analyzed with respect to correlation with pigment content. To compute an estimate of chlorophyll content multiple re-gression as well as neural net approach have been applied and both proved to be successful.